PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN PENCEGAHAN KARIES GIGI PADA ANAK USIA SEKOLAH DI MI MUHAMMADIYAH KALIPETUNG KABUPATEN BANYUMAS - Siti Haniyah (Viva Medika, 2013)
Background: Dental caries is the main problem of oral health are often found in children ofschool age, the prevalence of dental caries in Indonesia was about 90% of the 238 million ofIndonesian population and the number of children aged 15 years and under who sufferred fromdental caries reached 76,5%. Objective : This study aims to determine the effect of health education toward level ofknowledge on the prevention of dental caries for school age children in MI MuhammadiyahKalipetung.Method : This research used pe-eksperimental desaignn with one group pretest and posttestdesign. Sample were taken using cluster sampling. Respondent in this research is student inclass II until VI in MIMuhammadiyah Kalipetung, they are 55 respondents. The data wascollected using questionnaire. Analysis of data used SPSS program with Wilcoxon Signed RankTest.Result : The result showed the effect of health education toward level of knowledge on theprevention of dental caries with the value of p=0,037 (p<0,05).Conclusion : From the result of the analysis, it can be conclude that there effect of healtheduction toward level of knowledge on the prevention of dental caries for school age children inMI Muhammadiyah Kalipetung. Keywords: Dental caries, Health education, Age of school childen